2019
DOI: 10.1002/hep4.1362
|View full text |Cite
|
Sign up to set email alerts
|

Repression of MicroRNA‐30e by Hepatitis C Virus Enhances Fatty Acid Synthesis

Abstract: Chronic hepatitis C virus (HCV) infection often leads to end‐stage liver disease, including hepatocellular carcinoma (HCC). We have previously observed reduced expression of microRNA‐30e (miR‐30e) in the liver tissues and sera of patients with HCV‐associated HCC, although biological functions remain unknown. In this study, we demonstrated that HCV infection of hepatocytes transcriptionally reduces miR‐30e expression by modulating CCAAT/enhancer binding protein β. In silico prediction sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…( 25,40‐42 ) Furthermore, HCV‐induced lipogenesis contributes to the increased accumulation of LDs in cells, which facilitates virus assembly and secretion. ( 16,43 ) In this study, we showed that HCV RNA replication was significantly down‐regulated in Linc‐Pint overexpression. On the other hand, Linc‐Pint overexpression significantly reduced the de novo lipogenesis and LD accumulation in hepatocytes.…”
Section: Discussionmentioning
confidence: 61%
“…( 25,40‐42 ) Furthermore, HCV‐induced lipogenesis contributes to the increased accumulation of LDs in cells, which facilitates virus assembly and secretion. ( 16,43 ) In this study, we showed that HCV RNA replication was significantly down‐regulated in Linc‐Pint overexpression. On the other hand, Linc‐Pint overexpression significantly reduced the de novo lipogenesis and LD accumulation in hepatocytes.…”
Section: Discussionmentioning
confidence: 61%
“…The role of miR-30e in HCC development is thought to be through enhancement of autophagy leading to the development of HCC [25]. Recent studies have shown that miR-30e regulates the genes ATG5 and ATG12 which control the autophagy process [26]. Moreover, HOXA1, which has been recognized as a new miR-30e target, plays significant roles in regulating cell proliferation, carcinogenesis and metastasis [27].…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of miR-30e decreased the lipid synthesis-related proteins SREBP-1c and FASN in hepatocytes. It could also inhibit autophagy activation in HCV-infected hepatocytes [15]. In addition, it was also found that miR-30e could take part in HBVinduced liver brosis progression by targeting P4HA2 [16].…”
Section: Discussionmentioning
confidence: 99%